2019
DOI: 10.1038/s41598-019-56399-7
|View full text |Cite
|
Sign up to set email alerts
|

High prevalence of clarithromycin resistance and effect on Helicobacter pylori eradication in a population from Santiago, Chile: cohort study and meta-analysis

Abstract: Helicobacter pylori (H. pylori) eradication using standard triple therapy (STT) with proton pump inhibitors (PPI), amoxicillin and clarithromycin (CLA) has been the standard in Latin America. However, CLA resistance is a rising problem affecting eradication rates. Genetic polymorphisms of CYP2C19, a PPI metabolizer may also affect eradication. The primary aims of this study were to evaluate the effect of clarithromycin resistance on H. pylori eradication in a population from Santiago, and to establish the pool… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
0
6

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(29 citation statements)
references
References 44 publications
0
23
0
6
Order By: Relevance
“…Several studies have shown the eradication rates to be 75% 5 , 8 . Resistances to antibiotics, particularly clarithromycin, is the crucial factor affecting H. pylori eradication therapy 9 , 10 . The clarithromycin resistance rate has been found to be up to 50% in China 11 .…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have shown the eradication rates to be 75% 5 , 8 . Resistances to antibiotics, particularly clarithromycin, is the crucial factor affecting H. pylori eradication therapy 9 , 10 . The clarithromycin resistance rate has been found to be up to 50% in China 11 .…”
Section: Introductionmentioning
confidence: 99%
“…An unprecedented number of studies last year reported on the important topic of antimicrobial resistance of H pylori strains 24‐60 . These are outlined in Table 1.…”
Section: Antibiotic Resistancementioning
confidence: 99%
“…La tasa de infección varía según zona geográfica. Se estima que un 50% de la población mundial es portadora y en Chile más del 70% de los adultos estarían contagiados 11,12 . Existe una tendencia a la disminución en la prevalencia de H. pylori a nivel mundial, especialmente en países desarrollados y en niños 13 .…”
Section: Contextounclassified
“…De hecho, los consensos de América Latina, Toronto y Maastricht V recomiendan no usar la triterapia en zonas donde la resistencia a claritromicina sea mayor de 15% 5,16,19 . Estudios recientes demuestran que en Chile la resistencia a dicho antibiótico ha aumentado por sobre el 20% 12 . Frente a este problema, se ha generado una búsqueda de diferentes alternativas terapéuticas, libres de claritromicina, como la cuatriterapia con bismuto, adicionar metronidazol, o uso de altas dosis de amoxicilina 20 .…”
Section: Contextounclassified